Economic analysis of sweet potato (Ipomoea batata L.) farming in Lamongan regency. Issue 1 (January 2021) - Hamidah, E; Rahayu, E S; Sutrisno, J; Marwanti, S
Abstract: Sweet potato has the potential to be developed for diversified food consumption programs as a source of carbohydrates, nutrients, with a small risk of failure, low production costs, various processed products, food providers, industrial raw materials, and animal feed. This research aimed to analyze sweet potato farming economically and socially. The study was carried out quantitatively using a survey method. The research was conducted in Lamongan Regency, East Java, Indonesia. The location was chosen purposively. The sampling method was carried out using census in Kalitengah and Kedungpring Districts, in 6 villages, with 348 respondent farmers. The data analysis employed Revenue Cost (R/C) and descriptive analysis. The results revealed that 80.46% of farmers did not complete elementary school. Farmers with experience in sweet potato farming over 20 years reached 67.53%. Their income from total farm costs was IDR 5, 178, 296, with an R/C ratio is 1.89. Sweet potato farming is profitable and feasible to develop. The utilization of small sweet potato tubers affected by Cylas Formicarius disease as a fish feed was carried out by 19.54% of the farmers. Meanwhile, 51.72% of the farmers utilized sweet potato stalks and leaves as goat feed.